Quality ensured non‐orthogonal multiple access based downlink scalable video coding multicasting over cognitive radio network. Issue 1 (26th October 2021) - Dey, Sudipta; Misra, Iti Saha
Abstract: The combination of the cognitive radio network (CRN) and non‐orthogonal multiple access (NOMA) technologies for scalable video coding (SVC) can be considered as a promising approach for quality‐driven video transmission over a fifth‐generation (5G) network. Advanced techniques such as efficient channel allocation, advanced sensing strategy, and optimum power allocation can combinedly improve the overall system performance. In this context, we propose an intergroup content‐aware proportionate channel allocation policy, sensing time optimization strategy and quality of service (QoS) ensured intragroup power allocation scheme for downlink SVC multicasting over CRN using NOMA technology to enhance the quality of experience (QoE) of secondary users (SUs). We propose an optimum power allocation strategy for different NOMA layers to maximize the weighted sum rate of different SVC groups ensuring the individual QoS requirements. Although the power allocation problem seems to be nonconvex, however, it can be transformed into a convex function under some specific conditions which are discussed in this article. Extensive simulation reveals that our proposed power allocation scheme for NOMA with QoS constraint outperforms the other two conventional schemes, that is, NOMA fixed power allocation and NOMA without QoS constraint in terms of average weighted sum rate and average QoE of SUs. Abstract : In this article, a quality ensured NOMA based downlink SVC multicasting over CRN is proposed. This scheme combines three important aspects, that is, optimum channel allocation, sensing time optimization, and optimum power allocation for different NOMA layers with QoS requirements. The extensive simulation shows our proposed NOMA‐WQC outperforms the other two conventional schemes NOMA‐FPA and NOMA‐WOQC.